ANALISIS PENGENDALIAN KUALITAS PRODUK KOPI DENGAN MENGGUNAKAN METODE SEVEN TOOLS DI UMKM KOPI XYZ BANYUWANGI - Asfarina Hidayah; Dyah Fitri Ayu Kusniah (Journal of Industrial Engineering & Technology Innovation, 2026)
XYZ Coffee MSME in Banyuwangi is a coffee processing business that still faces product quality problems in the form of defects during the production and packaging processes. This study aims to analyze coffee product quality control using the Seven Tools method in order to identify the dominant types of defects and the factors causing defective products. The methods used in this study include check sheets, histograms, scatter diagrams, control charts, Pareto diagrams, and fishbone diagrams. The results showed that there were two types of product defects, namely broken coffee beans with 232 defects and peeling stickers with 311 defects during the period of September 2025 to January 2026. Based on the Pareto diagram results, the dominant defect was peeling stickers with a percentage of 57.3%, while broken coffee beans accounted for 42.7%. The p-chart calculation results indicated that the production process was still within statistical control limits with a Central Line (CL) value of 0.088. The main factors causing defects originated from human, method, material, and machine aspects, especially in the sticker installation process which was still carried out manually, resulting in less optimal adhesive strength. Therefore, the company needs to improve the sticker installation method, enhance the quality of adhesive materials, improve roasting machine settings, and increase worker accuracy in order to minimize the number of defective products.